Discontinuity Pragmatically Framed. - Gorman, Jonathan (Journal of the Philosophy of History, 2017)
This is an attempt to discover and clarify the philosophical nature of what Eelco Runia claims to be his new and up-to-date philosophy of history, a programme offered in his 2014 book Moved by the Past: Discontinuity and Historical Mutation. His suggestion that his argument is a "dance" is taken seriously, and following an analysis of historical "meaning" and its time-extended nature it is argued that the book's presentation commits Runia to a conception of meaning that requires more weight than he allows to the centrality of narrative understanding in history. His attempt to reconnect critical and substantive philosophies of history is analysed and criticised. His apparently inconsistent commitments to both Vico's verum-factum claim, where we can make history, and to Gumbrecht's "presence", where history can make us, is clarified in terms of a pragmatic philosophy that permits Runia to have the psychology-based approach that he relies upon.